Potential Analysis of Agricultural Sector in East Java with Klassen Typology Approach Method and LQ (Location Quotient) Year 2014-2017 - okta risky anggraini (Universitas Bangka Belitung, 2020)
The agricultural sector is a sector that supports the lives of most Indonesians. Therefore, the agricultural sector in Indonesia needs to continue to be developed in line with population growth and technological advancements to increase agricultural production. The production of agricultural products plays an important role in development, especially to meet domestic food consumption and also increase export income in Indonesia. Also, the agricultural sector is strategic in the structure of national economic development. Therefore, this research discusses the analysis of typology class and LQ analysis which is used as a reference in the development of the agricultural sector in East Java so that it can play a maximum role in increasing the GRDP of East Java in particular and the National GDP in general